The influence of relaxing and self-selected stimulating music on vertical jump performance in male volleyball players - Gavanda, S.; Hosang, T. J.; Wagener, S.; Sönmez, M.; Kayser, I.; Knicker, A. J. (International Journal of Exercise Science, 2022)
Most research concerning the effects of music on physical performance was conducted using endurance parameters. This study investigated the effects of relaxing (RLX) vs. self-selected stimulating music (SM) vs. no music (NM) on jump height (JH), jump power (PWR), and average rest period between jumps (RP) in 13 athletes (age: 25.5 ± 2.6 years). After a warm-up and listening to music (1 min) or NM, participants completed five squat jumps on a force plate. Psychological ratings of mood were assessed using a questionnaire before warm-up and after jumping. A one-way ANOVA was conducted to compare effects of music on JH, PWR, and RP. A Friedman test with Wilcoxon signed-rank test was used to detect changes in mood. There were no significant effects of music on JH (p = 0.162) and PWR (p = 0.162). A trend towards longer RP in RLX when compared to SM was detected (+2.72 s, +22%, p = 0.059, d = 0.35). Participants felt more "relaxed" (+3 ranks) and more "powerful" after listening to SM (+2 ranks). Following NM and RLX, athletes felt more "energetic" (each +3 ranks) but less energetic (-3 ranks) after SM. In conclusion, this study did not find any performance-enhancing effects of self-selected SM on jump performance. The influences of music on psychological ratings were inconclusive. For this reason, no evidence-based guidelines for the practical application of music in elite jumping athletes can be made, and more studies are warranted.